Organizational research methods : a guide for students and researchers - Brewerton, Paul.; Millward, Lynne (London ; Thousand Oaks, Calif. : SAGE, 2001)
Provides the reader with clear pointers for how to conduct organizational research appropriately, through planning and making informed and systematic research decisions, to understanding the ethical implications of applied organizational research, to implementing, reporting and presenting the findings to the highest possible standards.
IntroductionApplying Social Science to the Real WorldStarting Off the Research ProcessObtaining and Using Access to an OrganizationProject DesignMethods of Data CollectionSampling ConsiderationsAssessing Performance in OrganizationsData AnalysisReporting Research Findings
Includes bibliographical references and index.
Keywords: Organization -- Research -- Methodology; Organizational behavior -- Research; Organizational sociology -- Research